2022
DOI: 10.1007/s10869-022-09848-6
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Hate: How Nonwork Discrimination Experienced During the COVID-19 Pandemic Impacts Asian American Employees

Abstract: The COVID-19 pandemic has been accompanied by a sharp increase in prejudice and discrimination targeting Asian Americans in the USA. Thus, in addition to the public health risks associated with the virus, exposure to discrimination poses a unique threat to the health and well-being of Asian Americans. Indeed, empirical evidence has documented the linkage between experiencing anti-Asian discrimination during the pandemic and health decrements among Asian Americans. The goal of this study was to expand that rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…For example, Blacks are often viewed as aggressive and untrustworthy (Cooley & Payne, 2019), while Asians are often cited as the "model minority," which describes them as intelligent, hardworking, and economically successful (Rosette et al, 2018). However, Asians face stereotypes in other areas, such as accents (Geiger et al, 2023) and anti-Asian sentiment as a result of COVID-19 (Dhanani et al, 2023), and they have been shown to be evaluated less favorably than Whites in selection and promotion decisions, particularly for positions involving social skills (Lai & Babcock, 2013).…”
Section: Bias/discrimination Researchmentioning
confidence: 99%
“…For example, Blacks are often viewed as aggressive and untrustworthy (Cooley & Payne, 2019), while Asians are often cited as the "model minority," which describes them as intelligent, hardworking, and economically successful (Rosette et al, 2018). However, Asians face stereotypes in other areas, such as accents (Geiger et al, 2023) and anti-Asian sentiment as a result of COVID-19 (Dhanani et al, 2023), and they have been shown to be evaluated less favorably than Whites in selection and promotion decisions, particularly for positions involving social skills (Lai & Babcock, 2013).…”
Section: Bias/discrimination Researchmentioning
confidence: 99%
“…Studies have shown that perceived racial discrimination has negative impacts on psychological well-being and racial identity among all racial minorities [ 12 , 13 ]. Similarly, COVID-19-related racial discrimination has contributed to mental distress among AAs, including depressive symptoms [ 10 , 14 , 15 , 16 , 17 ], anxiety [ 10 , 18 ], and psychological distress [ 19 , 20 ]. A multiracial qualitative study reported that COVID-19-related anti-Asian discrimination caused fear, anxiety/distress, hopelessness/depression, and avoidance in all participants, regardless of their race [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Upon reflection there were more pandemic related stressors that would have been interesting to investigate. For example, later research has demonstrated that the pandemic led to a rise in anti-Asian discrimination (Dhanani et al, 2022), the worsening of many individuals' pre-existing physical and mental health conditions (Bailey et al, 2021) and the cancellation or postponement of important events . These stressors are also likely to impact the mental health and suicide risk of individuals and would be worthy of future investigation.…”
Section: Limitationsmentioning
confidence: 99%